Special speed-power training as the basis of technical skillfulness improvement in sport aerobic - Moshenska, T. V.; Bodrenkova, I. A. (Pedagogics, psychology, medical-biological problems of physical training and sports, 2015)
Purpose: to theoretically work out and experimentally substantiate effectiveness of authors` methodic of speed-power qualities` training in sport aerobic. Material: 20 sportsmen participated in the research: boys and girls of 8-12 years` age. Assessment of speed-power fitness was conducted by results of commonly accepted tests, applied in sport practice. Results: we have developed complexes of jump exercises, which envisage varying of conditions of exercises` fulfillment at the account of pushing conditions (jumps in depth, jumps over obstacles and jumps on elevated platforms). When fulfilling jumps in motion the main was achievement of maximal height with fixing of jump`s form in flight. Conclusions: we offer six complexes of exercises for speed-power training in sport aerobic. These complexes are recommended to be fulfilled at the end of preparatory part of training session during 15-20 minutes.